CRAGE-CRISPR facilitates rapid activation of secondary metabolite biosynthetic gene clusters in bacteria. Issue 4 (21st April 2022) - Ke, Jing; Robinson, David; Wu, Zong-Yen; Kuftin, Andrea; Louie, Katherine; Kosina, Suzanne; Northen, Trent; Cheng, Jan-Fang; Yoshikuni, Yasuo
Summary: With the advent of genome sequencing and mining technologies, secondary metabolite biosynthetic gene clusters (BGCs) within bacterial genomes are becoming easier to predict. For subsequent BGC characterization, clustered regularly interspaced short palindromic repeats (CRISPR) has contributed to knocking out target genes and/or modulating their expression; however, CRISPR is limited to strains for which robust genetic tools are available. Here we present a strategy that combines CRISPR with chassis-independent recombinase-assisted genome engineering (CRAGE), which enables CRISPR systems in diverse bacteria. To demonstrate CRAGE-CRISPR, we select 10 polyketide/non-ribosomal peptide BGCs in Photorhabdus luminescens as models and create their deletion and activation mutants. Subsequent loss- and gain-of-function studies confirm 22 secondary metabolites associated with the BGCs, including a metabolite from a previously uncharacterized BGC. These results demonstrate that the CRAGE-CRISPR system is a simple yet powerful approach to rapidly perturb expression of defined BGCs and to profile genotype-phenotype relationships in bacteria. Graphical abstract: Highlights: An expansion of the CRISPR toolbox by implementing it on CRAGE Gene-to-compound approach in non-model bacteria to characterize BGC and regulator CRAGE-CRISPRd/CRISPRa mediate loss- and gain-of-function studies of BGCs Target sites for CRISPRa with varied gRNAs show variable levels of BGC activation Abstract : Ke et al. develop a CRAGE-CRISPR approach, which allows loss- and gain-of-function studies to rapidly confirm activity of six secondary metabolite biosynthetic gene clusters (BGCs). These results prove that CRAGE-CRISPR is a simple but effective strategy to study BGC activities in various microorganisms.